Meta-Analysis of Randomized Controlled Trials Using Botulinum Toxin A at Different Dosages for Urinary Incontinence in Patients With Overactive Bladder - Gong, Qin-Qin; Xu, Yu-Qiong; Xu, Jun; Ding, Xiao-Yan; Guo, Chong (Frontiers in Pharmacology, 2020)
Background: Urinary incontinence (UI) is a common and refractory complication for patients with neurogenic detrusor overactivity (NDO) or idiopathic overactive bladder (IOAB). Objectives: To evaluated the effect of Botulinum toxin A (BTX-A) based on different dosages strategy for UI. Method: The MEDLINE, Ovid EMbase, The Cochrane Central Register of Controlled Trials (CENTRAL), China National Knowledge Internet (CNKI) and WanFang database were searched for relevant published randomized controlled trials (RCTs) between 1969 to September 31, 2018. All databased were searched to identify relevant Randomized controlled trials (RCTs) that investigated the clinical benefit of BTX-A for management of UI in patients with NDO and IOAB. Results: This meta-analysis involved nineteen original studies. The BTX-A was superior to placebo in reducing episodes of UI for NDO patients in all subgroups of different dosages for different durations, and also reduced maximum detrusor pressure in all kinds of 200U and 300U at 6 weeks. However, it increased post void residual in different dosages of 200U at 2 weeks. For IOAB patients, compared to placebo, BTX-A increased detrusor compliance for different dosages of 200U and 300U at 12 and 36 week, but it increased risk of urinary tract infections at other dosages. Conclusions: This meta-analysis indicated that BTX-A 200U and 300U are more effective than placebo in the treatment of NDO, with minimal, local, and manageable adverse events. Furthermore, BTX-A 300U and 200U could also improve detrusor compliance of IOAB. However, more RCTs would still be necessary to explore the effect of BTX-A on management of UI in NDO and IOAB patients.